Phonemic consonant sounds in modern standard Arabic - Salameh, Mohammad Yahya Ali Bani (Linguistics and Culture Review, 2021)
Consonants are vital to the phonetic pattern of Modern Standard Arabic (MSA). There are 28 consonants throughout MSA, and they are divided into groups based on where and how they are articulated. The examination of consonants throughout MSA is the focus of this work. This report’s underpinning is the clarification of the phonetic principles underlying sound categorization. This shows the main limitation, which is primarily the use of phonetic instead of phonology descriptions of sounds. The Standard Arabic (SA) consonant sounds are included after this categorization effort, in addition to an operative word to every consonant. Location, style of articulation, and tone are the requirements for definition. Findings showed that numerous Arabic sounds have increasingly deviated from the norm while using alphabets as the textual symbols for reproducing the real pronunciation of the phonemes. With respect to this specific version the research extended even beyond the phonetic aspect of Arabic consonant, addressing a number of relevant problems, such as the dispersion of Arabic consonant, the varieties of Arabic consonants, as well as the phonetic specification of Arabic consonants.